Genome characterization of a uropathogenic Pseudomonas aeruginosa isolate PA_HN002 with cyclic di-GMP-dependent hyper-biofilm production - Lin, Siying; Chen, Shuzhen; Li, Li; Cao, Huiluo; Li, Ting; Hu, Ming; Liao, Lisheng; Zhang, Lian-Hui; Xu, Zeling (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudomonas aeruginosa can cause various types of infections and is one of the most ubiquitous antibiotic-resistant pathogens found in healthcare settings. It is capable of adapting to adverse conditions by transforming its motile lifestyle to a sessile biofilm lifestyle, which induces a steady state of chronic infection. However, mechanisms triggering the lifestyle transition of P. aeruginosa strains with clinical significance are not very clear. In this study, we reported a recently isolated uropathogenic hyper-biofilm producer PA_HN002 and characterized its genome to explore genetic factors that may promote its transition into the biofilm lifestyle. We first showed that high intracellular c-di-GMP content in PA_HN002 gave rise to its attenuated motilities and extraordinary strong biofilm. Reducing the intracellular c-di-GMP content by overexpressing phosphodiesterases (PDEs) such as BifA or W909_14950 converted the biofilm and motility phenotypes. Whole genome sequencing and comprehensive analysis of all the c-di-GMP metabolizing enzymes led to the identification of multiple mutations within PDEs. Gene expression assays further indicated that the shifted expression profile of c-di-GMP metabolizing enzymes in PA_HN002 might mainly contribute to its elevated production of intracellular c-di-GMP and enhanced biofilm formation. Moreover, mobile genetic elements which might interfere the endogenous regulatory network of c-di-GMP metabolism in PA_HN002 were analyzed. This study showed a reprogrammed expression profile of c-di-GMP metabolizing enzymes which may promote the pathoadaption of clinical P. aeruginosa into biofilm producers.